First book marketplace - Eckert, Alisia, (SAGE knowledge. Cases., 2016)
Kyle Zimmer and her colleagues founded First Book in 1992. A nonprofit organization dedicated to providing children from low-income households with the chance to read and own their first new books, First Book reaches children in need by providing new books to community preschool, after-school, and literacy programs. In 2005, First Book marked the delivery of its 40 millionth book, having successfully reached children in communities across the country. However, like her counterparts at other literacy organizations, Kyle worked within the bounds of overwhelming demand and limited resources. Despite its success, First Book was able to provide only a fraction of the quantity of free books requested by eligible programs. This case study discusses this important topic.